The Influence of Convection Group Marketing Through Social Media on Brand Equity and Consumer Behavior Through Purchase Intent as an Intervening Variable - Ifah Zuliarti; Abid Muhtarom; Titin Titin (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2024)
This study aims to analyze the influence of garment group marketing through social media—encompassing online promotion (X1), price (X2), and marketing activities (X3)—on brand equity (Y1) and consumer attitude (Y2) with purchase intention (Z) as an intervening variable. The study employs a descriptive quantitative approach with 30 consumers who had purchased through Facebook within the past 6 months, selected via purposive sampling. Data were collected through Likert-scale questionnaires (1–5) and analyzed using PLS-SEM with SmartPLS 3. Results indicate that: (1) online promotion does not significantly affect brand equity (p=0.201), consumer attitude (p=0.347), or purchase intention (p=0.545); (2) price does not significantly affect brand equity (p=0.921) or consumer attitude (p=0.073), but significantly affects purchase intention (p=0.000); (3) marketing activities significantly affect brand equity (p=0.021), consumer attitude (p=0.000), and purchase intention (p=0.022); (4) purchase intention significantly affects brand equity (p=0.018) and consumer attitude (p=0.039); (5) price affects brand equity and consumer attitude through full mediation by purchase intention. These findings imply that garment groups need to optimize integrated marketing activities and set competitive pricing to stimulate purchase intention, which in turn enhances brand equity and positive consumer attitudes.